Characterization of the Kynurenine Pathway and Quinolinic Acid Production in Macaque Macrophages. (January 2013) - Lim, Chai K.; Yap, Margaret M.C.; Kent, Stephen J.; Gras, Gabriel; Samah, Boubekeur; Batten, Jane C.; De Rose, Robert; Heng, Benjamin; Brew, Bruce J.; Guillemin, Gilles J.
The kynurenine pathway (KP) and one of its end-products, the excitotoxin quinolinic acid (QUIN), are involved in the pathogenesis of several major neuroinflammatory brain diseases. A relevant animal model to study KP metabolism is now needed to assess whether intervention in this pathway may improve the outcome of such diseases. Humans and macaques share a very similar genetic makeup. In this study, we characterized the KP metabolism in macaque primary macrophages of three different species in comparison to human cells. We found that the KP profiles in simian macrophages were very similar to those in humans when challenged with inflammatory cytokines. Further, we found that macaque macrophages are capable of producing a pathophysiological concentration of QUIN. Our data validate the simian model as a relevant model to study the human cellular KP metabolism in the context of inflammation.